Methyl-CpG-binding protein 2 (MECP2) mutation type is associated with disease severity in Rett syndrome. Issue 3 (7th January 2014) - Cuddapah, Vishnu Anand; Pillai, Rajesh B; Shekar, Kiran V; Lane, Jane B; Motil, Kathleen J; Skinner, Steven A; Tarquinio, Daniel Charles; Glaze, Daniel G; McGwin, Gerald; Kaufmann, Walter E; Percy, Alan K; Neul, Jeffrey L; et al.
Abstract : Background: Rett syndrome (RTT), a neurodevelopmental disorder that primarily affects girls, is characterised by a period of apparently normal development until 6–18 months of age when motor and communication abilities regress. More than 95% of individuals with RTT have mutations in methyl-CpG-binding protein 2 (MECP2), whose protein product modulates gene transcription. Surprisingly, although the disorder is caused by mutations in a single gene, disease severity in affected individuals can be quite variable. To explore the source of this phenotypic variability, we propose that specific MECP2 mutations lead to different degrees of disease severity. Methods: Using a database of 1052 participants assessed over 4940 unique visits, the largest cohort of both typical and atypical RTT patients studied to date, we examined the relationship between MECP2 mutation status and various phenotypic measures over time. Results: In general agreement with previous studies, we found that particular mutations, such as p.Arg133Cys, p.Arg294X, p.Arg306Cys, 3° truncations and other point mutations, were relatively less severe in both typical and atypical RTT. In contrast, p.Arg106Trp, p.Arg168X, p.Arg255X, p.Arg270X, splice sites, deletions, insertions and deletions were significantly more severe. We also demonstrated that, for most mutation types, clinical severity increases with age. Furthermore, of the clinical features of RTT, ambulation, hand use and age at onset of stereotypies are strongly linked to overall disease severity. Conclusions: We have confirmed that MECP2 mutation type is a strong predictor of disease severity. These data also indicate that clinical severity continues to become progressively worse regardless of initial severity. These findings will allow clinicians and families to anticipate and prepare better for the needs of individuals with RTT.